Nationally Determined Contributions (NDCs) Capacity Scorecard: scoping study for East and Southern Africa (ESA) - Jacobs-Mata, Inga; Wamukoya, G.; Nkosi, Mahlatse; Denje, T. M.; Roman, Henry; Awolala, D. O.; Ires, Idil; Auma, S. A.; Chepcheng, L.; Meltus, Q. J.; Karanja, L.; Okelo, C.; et al. (International Water Management Institute (IWMI), 2024)
Nationally Determined Contributions (NDCs) are central to the Paris Agreement, requiring countries to set and communicate climate action targets every five years. NDCs are formulated through a bottom-up process considering national circumstances and priorities, providing a framework for economic development and poverty eradication aligned with climate goals. The process includes comprehensive stakeholder engagement, encompassing government bodies, civil society, academia, and the private sector. As the world gears up for the development of the Next Generation of NDCs in 2025, an important partnership between the International Water Management Institute (IWMI) and the African Group of Negotiators Expert Support (AGNES), made possible through the CGIAR’s Regional Integrated Initiative for East and Southern Africa (ESA), Ukama Ustawi, has sought to provide technical support to the process and assess the capacity of countries to implement the NDC’s in various sectors through a NDC Capacity Scorecard.